Proceso de atención de enfermería en lactante mayor con gastroenteritis aguda. - Ninabanda Agualongo, Jessica Maura (2023)
Acute gastroenteritis Acute gastroenteritis is a self-limited cause that consists of a decrease in fever, vomiting, and abdominal pain as the frequency and consistency of your stools increases. Its most common etiology is of viral origin, with rotavirus being the main cause of diarrhea worldwide of bacterial and parasitic origin. Risk factors that contribute to severity and susceptibility include: Overcrowding, malnutrition, and poor socioeconomic conditions in which they live. Babies and children under 5 years of age are more likely to become dehydrated. The diagnosis of acute diarrhea in infants and children requires careful evaluation and a detailed history to distinguish intestinal infection from other causes. Faced with an infant and/or child with acute diarrhea, a global assessment and detailed anamnesis are necessary in order to differentiate enteric infection from other causes that induce diarrhea and vomiting. Next, the clinical case of an elderly infant who is admitted to the Alfredo Noboa Montenegro Hospital with a diagnosis of gastroenteritis will be studied to ensure the appropriate intervention to follow as nurses for his speedy recovery.